Returns to Shareholder Activism: Evidence from a Clinical Study of the Hermes UK Focus Fund - Becht, Marco; Franks, Julian; Mayer, Colin; Rossi, Stefano (Review of Financial Studies, 2010)
This article reports a unique analysis of private engagements by an activist fund. It is based on data made available to us by Hermes, the fund manager owned by the British Telecom Pension Scheme, on engagements with management in companies targeted by its UK Focus Fund. In contrast with most previous studies of activism, we report that the fund executes shareholder activism predominantly through private interventions that would be unobservable in studies purely relying on public information. The fund substantially outperforms benchmarks and we estimate that abnormal returns are largely associated with engagements rather than stock picking.